Comparing the Diagnostic Efficacy of Different Calcitonin Stimulation Tests for Sporadic Medullary Thyroid Carcinoma: Calcium Gluconate vs. Calcium Chloride - Jovan Ilic; Katarina Tausanovic; Goran Zoric; Milan Jovanovic; Matija Buzejic; Sara Ivanis; Milan Parezanovic; Milan Marinkovic; Nemanja Karamarkovic; Ana Petakov; Vladan Zivaljevic (Diagnostics)
Background: Medullary thyroid carcinoma (MTC) is a rare malignancy derived from parafollicular C-cells, with calcitonin (Ct) as its key biomarker. While basal Ct (bCt) levels above 100 pg/mL strongly suggest MTC, intermediate elevations (10–100 pg/mL) may reflect C-cell hyperplasia (CCH) or other benign conditions, making diagnostics challenging. Although calcium stimulation testing enhances sensitivity, the optimal cut-off values and comparative efficacy of calcium gluconate (CG) versus calcium chloride (CC) remain insufficiently researched. Methods: Data on 176 patients who underwent total thyroidectomy between 2009 and 2025 were retrospectively analyzed. BCt values ranged from 10 to 100 pg/mL, and stimulated Ct (sCt) values were above 100 pg/mL. CG was used from 2009 to 2019, and CC was used from 2020 to 2025. Definitive pathohistological findings divided patients into those with MTC, CCH, or no C-cell pathology. Receiver operating characteristic (ROC) analysis identified optimal Ct thresholds for predicting MTC for each stimulatory agent. Results: Of the 176 patients, 36 (20.5%) had confirmed MTC. A bCt threshold of 31.1 pg/mL yielded 69.4% sensitivity and 87.1% specificity. For sCt, optimal cut-offs were 810.8 pg/mL for CG and 1076 pg/mL for CC. Lower thresholds (388.4 pg/mL for CG and 431.5 pg/mL for CC) improved sensitivity (≥76.9%) and negative predictive value (>91%). Conclusions: Calcium stimulation testing improves MTC detection in patients with moderate bCt elevation. Although CG showed marginally better diagnostic performance, CC remains a practical and reliable alternative, especially when higher cut-off values are considered. Early surgical intervention should be considered when sensitivity-driven thresholds are met.